REVISITING THE RESPONSIBILITY TO PROTECT AS AN INTERNATIONAL NORM - Swatilekha Bhattacharya (Journal of International Studies, 2022)
The purpose of the paper is to revisit the origin of the principle of responsibility to protect (R2P) focusing on few cases and reflecting on the troubled journey that it has made maneuvering its structural constraints posed by hegemonic powers and geopolitical manipulations, by employing historical methods in tracking its evolution. The inter-state aggression during the Cold War, largely gave way to war and violence within, after the end of it, rather than between, states. There were two opposing views at the United Nations (UN): those who supported right of humanitarian intervention and those who viewed such a doctrine as an infringement upon national sovereignty. In this regard, R2P remains a developing principle and, the absence of definitive state practice in this area means that states wanting to intervene to protect foreign populations from atrocities are left without clear legal justification for such action. In the absence of UN Security Council authorisation, use of force under the banner of R2P remains contentious. Lastly, the paper discusses the prospects the principle will have in future as constraints and manipulations are still present.